(untitled) (Raparin Journal of Humanities (RJH), 2025)
Postmodernism, an impactful artistic movement from the 1960s to the 1990s, critiques modern art while accepting various art forms and critical philosophies. It, however, places focus on modern day art and its meaning far beyond the traditional framework. In the case of Kurdistan, Postmodernism comes with these traits alongside the Kurdish cultural heritage and history. It is honest to note that Kurdish artists strive to illustrate the delicate balance of the Kurdish society and identity through a rich tapestry of common experiences and memories. In Kurdistan, Postmodernism is an expedition of innovative self-exploration and continuing inquiry. It aims to intend to provide a perspective that enables wider artistic freedom while upholding the essence of Kurdish culture. In this context, the Kurdish art is continuously encouraged to actively participate in the universal dialogue about art and culture.